Perceived Entrepreneurial Sustainability and Financial Stability Among Fashion Designers in Abia State, Nigeria - Daniel Nwaozuru; Chiamaka A. Chukwuone; Rachael A. Wonah; Mellah E. Uzoamaka (International Journal of Home Economics, Hospitality and Allied Research, 2024)
This research explore factors influencing entrepreneurial sustainability and financial stability within the context of the fashion industry, with a focus on the perceptions of fashion designers in Abia State. Descriptive survey methods were employed to provide a comprehensive understanding of the subject matter. The total population for the study was 487, which comprises all registered fashion designers operating in Aba, hence the whole population was used for the study. The study was carried out in Aba which is one of the major fashion hubs in Abia State. Data was collected through structured questionnaire titled Questionnaire on Perceived Entrepreneurial Sustainability and Financial Stability among Fashion Designers (QPESFAFD). The data collected was analyzed using mean and standard deviation to answer the items on each objective. The findings revealed that there are perceived entrepreneurial sustainability strategies adopted by fashion designers, and perceptions influence the financial stability of fashion businesses. It also revealed that there are challenges and opportunities faced by fashion designers in sustaining their businesses and achieving financial stability. Based on the findings, recommendations were made that, there should be regular workshops and training sessions that will focus on financial management and planning specifically tailored for fashion designers and networking and collaboration platforms should facilitate knowledge sharing, resource pooling, and collaboration among fashion designers in Abia State